Proposta de indicadores de competitividade em sistemas de produção leiteiros : um estudo para as mesorregiões oeste, norte central e centro oriental do estado do Paraná - Brito, Marcel Moreira de (2018)
Every year, dairy farming has played an important role in the national and global agribusiness scenario, highlighting itself as an economically and socially important alternative. Currently Brazil is the fourth largest producer of milk in the world, driven mainly by the main producing States, such as Minas Gerais, Paraná, Rio Grande do Sul, Goiás and Santa Catarina. Such apparent success is due to the degree of competitiveness of the chain compared to other activities and other important milk producers; however, after institutional changes since the 1990s, many milk producers, mostly small-scale, have abandoned the activity and even the rural milieu because they cannot adapt to the new requirements and market structure. Given the importance of competitiveness in the face of the success or failure of agents and even of the entire production chain, this study seeks to create competitiveness indicators; using primary data collected from producers in the State of Paraná, created using the multivariate statistical analysis method, factorial analysis, as well as to analyze the competitiveness of the different dairy production systems (SPL) of the three Mesoregions of Paraná State. Data were collected in 204 SPL in the West, Central North and Eastern Central Mesoregions of Paraná State, three important Mesoregions State production, and semi-structured questionnaires were applied in loco. The correlation analysis was performed to identify a significant number of significant correlations, after which the factorial analysis was used to reduce the data and create indicators, which extracted eight factors of competitiveness by the method of factorial scores, from 27 variables; Finally, the analysis of variance verified a difference between the mean values of the indicators for the SPL of the three Mesoregions studied (p?0.05). The analysis revealed statistical equality between SPL for the competitiveness indicators "Knowledge of the institutional environment", "Quality of transport" and "Infrastructure and support"; that is, the SPL studied are competitively the same for these indicators. However, statistical differences were identified for the competitiveness indicators "Market Transactions and Incentives", "Production Capacity and Economics of Scale", "Technology", "Diversification" and "Training and Technical Assistance" among the SPLs of the Mesoregions studied. Thus, the SPLs located in the Eastern Central Mesoregion showed greater competitiveness, with emphasis on the "T & IM" Transaction and Incentive indicators; Productive Capacity and Economies of Stairs "CP & EE", Knowledge and Technical Assistance "C & AT" and Technology "TEC"; followed by the West Mesoregion, of which the "TEC" and Diversification "DIV" competitiveness indicators stood out; and the SPL of the Central North of Paraná as the ones with the lowest competitiveness, underscoring the greater competitiveness deficiency in the "T & IM" and "TEC" Technology Transactions and Incentives indicators